Evenness of Dietary Protein Intake Is Positively Associated with Lean Mass and Strength in Healthy Women. (June 2022) - Johnson, Nathaniel R; Kotarsky, Christopher J; Mahoney, Sean J; Sawyer, Bailee C; Stone, Kara A; Byun, Wonwoo; Hackney, Kyle J; Mitchell, Steven; Stastny, Sherri N
Background: Evenness of protein intake is associated with increased lean mass, but its relationship with muscle strength and performance is uncertain. Objectives: We determined the association of evenness of protein intake with lean mass, muscle strength and endurance, and functional ability. Design: This was a cross-sectional study. Setting: Data were collected at a research university in the upper midwestern United States. Participants: One hundred ninety-two healthy women, aged 18 to 79 years, mean ± SEM 41.9 ± 1.3, completed the study. Measurements: Dietary intake was assessed using 3-day food diaries verified with food frequency questionnaires. To assess evenness of protein intake, the day was divided into 3 periods: waking to 11:30, 11:31 to 16:30, and after 16:30. Lean mass was measured with dual energy X-ray absorptiometry. Lower-body muscle strength and endurance were determined using isokinetic dynamometry. Upper-body muscle strength was maximal handgrip strength. Functional ability was assessed using 6-m gait speed and 30-second chair stand tests. Accelerometry measured physical activity. Results: Intakes of 25 g or more of protein at 1 or more of the 3 periods was positively associated with lean mass (β ± S.E.; 1.067 ± 0.273 kg, P < .001) and upper-body (3.274 ± 0.737 kg, P < .001) and lower-body strength (22.858 ± 7.918 Nm, P = .004) when controlling for age, body mass index, physical activity, and energy and protein intakes. Consuming at least 0.24 g/kg/period for those under 60 years and 0.4 g/kg/period for those 60 years and older was related to lean mass (0.754 ± 0.244 kg, P = .002), upper-body strength (2.451 ± 0.658 kg, P < .001), and lower-body endurance (184.852 ± 77.185 J, P = .018), controlling for the same variables. Conclusions: Evenness of protein intake is related to lean mass, muscle strength, and muscular endurance in women. Spreading protein intake throughout the day maximizes the anabolic response to dietary protein, benefiting muscle mass and performance.